Modeling Kelvin wake imaging mechanism of visible spectral remote sensing. (August 2021) - Song, Mingzhu; Wang, Shiyao; Zhao, Penglu; Chen, Yantong; Wang, Junsheng
Abstract: Kelvin wake is an important detection target of ocean visible spectral remote sensing. In the case of slow ship speed and low atmospheric transmissivity, the wake signal is weak and the SNR (Signal-Noise Ratio) is low. Therefore, the image obtained by the visible spectral remote sensing imaging system is often "unclear". In order to solve the problems above, this paper carries out the modeling of Kelvin wake imaging mechanism of visible spectral remote sensing. The Kelvin wake reflection distribution characteristics of rough sea surface are simulated based on the hydrodynamic model of Kelvin wake and the probability density distribution of rough sea surface, and a method to quantify the reflectance resolution for Kelvin wake imaging of rough sea surface is proposed. The changes in reflectance resolution caused by different wind speeds, ship parameters, source angle, receiver angle are also analyzed. Then the imaging link model of TDI-CCD (Time Delay and Integration Charge Coupled Devices) imaging system was established. The imaging results of a Kelvin wake reflected on the rough sea surface are simulated, and the impact of the changes of main imaging parameters (optical system F number, quantization bits, integration stages) on the imaging results of a Kelvin wake at different reflectance resolutions are analyzed. The research has clarified the mechanism of the visible spectral remote sensing system to clearly imaging the Kelvin wake, which can provide guidance on parameters design and attitude planning for the ocean visible spectral remote sensing system, and improve the ability of the imaging system to detect weak wake signals.